THE THEORETICAL FEASIBILITY OF SELF UNDERSTANDING EVALUATION SHEET IN GENETIC MATERIAL - PUTRI NUUR MASITA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Genetics and Protein Synthesis substance is the subject matter in the subjects of biology at the high school level who have the abstract characteristics that require creativity teacher. One effort to facilitate understanding of the material through the use of Understanding Self Evaluation Sheet (SUES) based on metacognitive. The research objective to produce SUES and describe its theoretical feasibility based on the expert. This research uses development model of Borg and Gall which consists of two step, step of a preliminary study and development. The results showed that the developed SUES get the review was 98.00%, which means SUES expressed very feasible in theory. Key words: SUES, metacognitive, TAI model, genetic substance and protein synthesis